Effects of the Digital Transition in Passenger Transport - an Analysis of Energy Consumption Scenarios in Europe - Michel Noussan (Fondazione Eni Enrico Mattei (FEEM), 2019)
The transport sector has rarely seen disruptive evolutions after the diffusion of the internal combustion engine, and today the European mobility is still heavily relying on oil derivates and on private cars. However, there is a significant push in cities towards more sustainable mobility paradigms, and digital technologies are playing a major role in unleashing possible alternatives to a car- and fossil-based mobility. Three major digital trends can be highlighted, with different levels of maturity and some potential synergies among them: Mobility as a Service, Shared Mobility and Autonomous Vehicles. The effects of these trends are also related to the strong push towards electric mobility, which currently appears as the most supported solution by companies and regulators to decarbonize the transport sector. This working paper discusses an investigation of the potential effects of digital transition, by means of a data-driven model for the calculation of the impacts of mobility demand in Europe in terms of primary energy consumption and CO2 emissions. The results show that digitalization may have a positive effect on energy consumption and CO2 emissions for passenger transport, given the strong efficiency improvements expected by technological development in the vehicles powertrains. The benefits are maximized if digital technologies are used towards a collective optimization, by increasing the share of available mobility options. Conversely, if digital technologies are limited to increase the quality of private mobility, the environmental benefits will likely remain very limited. Thus, there is a need of tailored policies supporting the right mobility models to fully exploit the potential benefits of digitalization.
Keywords: L91; O33; Q4; R41; 330; Digitalization; Transport; Energy Consumption; Energy Modelling